2020
DOI: 10.1101/2020.10.05.20207407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cycles of self-reported seizure likelihood correspond to yield of diagnostic epilepsy monitoring

Abstract: Objective: Video-electroencephalography (vEEG) is an important component of epilepsy diagnosis and management. Nevertheless, inpatient vEEG monitoring fails to capture seizures in up to one third of patients during diagnostic and pre-surgical monitoring. We hypothesized that personalized seizure forecasts could be used to optimize the timing of vEEG and improve diagnostic yield. Methods: We used a database of ambulatory vEEG studies to select a cohort with linked electronic seizure diaries of more than 20 repo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Hence, patient seizure diaries will remain a useful tool in clinical settings, and non-invasive forecasting systems based on mobile and wearable devices are desired by the epilepsy community ( 43 , 44 ). Wearable sensors and non-invasive features may be useful to forecast seizure likelihood ( 25 , 45 , 46 ), and self-reported events and biomarkers derived from wearables also demonstrate cycles that are co-modulated with seizure likelihood ( 30 , 38 , 40 ). However, the correlation between self-reported events and electrographic events is patient-specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, patient seizure diaries will remain a useful tool in clinical settings, and non-invasive forecasting systems based on mobile and wearable devices are desired by the epilepsy community ( 43 , 44 ). Wearable sensors and non-invasive features may be useful to forecast seizure likelihood ( 25 , 45 , 46 ), and self-reported events and biomarkers derived from wearables also demonstrate cycles that are co-modulated with seizure likelihood ( 30 , 38 , 40 ). However, the correlation between self-reported events and electrographic events is patient-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Cycles in seizure times were detected using a similar approach to our previous work ( 29 , 38 ). We assessed the phase locking of seizure times to a range of possible cycles using both the Omnibus test ( p < 0.05) and the synchronization index (SI ≥ 0.4) value to quantify phase locking.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated impressive seizure forecasting performance using multiday cycles measured from implantable EEG (114,115), although prospective validation is needed. Cycles of seizure likelihood can also be measured from selfreported seizure times (116), and for a subset of people, cycles measured from seizure diaries are predictive of the likelihood of electrographic seizures and epileptic activity (116,117). Machine learning can also be used with historic trends from self-reported seizure diaries, which may be useful to forecast future reported seizures (118,119).…”
Section: Patterns and Rhythms In Seizure Probabilitymentioning
confidence: 99%
“…Both cyclic and machinelearning approaches have been shown to accurately forecast seizures (or, more specifically, seizure diary events) in both focal and generalized epilepsies. Despite inaccuracy in individual seizure reporting, long-term patterns and cycles may still be accurately inferred for many individuals (116,117). Due to the indications for use of who can have implanted EEG for long-term recording, the existence of cycles has largely been validated electrographically in individuals with focal epilepsies.…”
Section: Patterns and Rhythms In Seizure Probabilitymentioning
confidence: 99%
“…Cycles in seizure times were detected using a similar approach to our previous work (29,38). We assessed the phase locking of seizure times to a range of possible cycles using both the Omnibus test (p < 0.05) and the synchronisation index (SI ≥ 0.4) value to quantify phase locking.…”
Section: Methodsmentioning
confidence: 99%